A Case of Philadelphia Chromosome Positive Myeloproliferative Neoplasm in a Pregnant Woman with Unusual Primary Myelofibrosis Features. (25th May 2013) - Koshy, Jason; Alperin, Jack; Jana, Bagi; Markowitz, Avi; Qian, You-Wen
Abstract : Myeloproliferative neoplasms (MPNs) are traditionally separated into BCR-ABL -positive chronic myeloid leukemia (CML), and BCR-ABL-negative MPNs including primary myelofibrosis (PMF), essential thrombocythemia (ET), and so forth. One of the diagnostic requirements for PMF and ET is the absence of the Philadelphia chromosome, while its presence is almost universally indicative of CML. However, a diagnostic dilemma arises when Philadelphia chromosome-positive MPNs lack the majority of the typical features seen in CML. Some of these classic CML features include basophilIa, marked leukocytosis, neutrophils left-shift with myelocytes bulge, and "dwarf" megakaryocytes. Presented here is a case of a 32-year-old pregnant patient who did not have typical morphologic findings for CML, and yet the Philadelphia chromosome was positive. The patient demonstrated some pathologic features that are commonly presented in PMF that included bone marrow reticulin fibrosis, leukoerythroblastosis, splenomegaly, and increased serum lactate dehydrogenase.